Host–guest-driven color change in water: influence of cyclodextrin on the structure of a copper complex of poly((4-hydroxy-3-(pyridin-3-yldiazenyl)phenethyl)methacrylamide-co-dimethylacrylamide) - Retzmann, Nils; Maatz, Gero; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2014)
In the present work we report the synthesis of poly((4-hydroxy-3-(pyridin-3-yldiazenyl)phenethyl)methacrylamide-co-dimethylacrylamide) and its reversible optical and complex-forming properties due to copper and cyclodextrin (CD) interactions. Color changing effects are characterized by UV–vis spectroscopy and the supramolecular behavior is investigated by dynamic light scattering experiments.
Keywords: cyclodextrin; copolymer; copper(II) sulfate; supramolecular; water complex

(untitled) - Gil, E. S.; Hudson, S. M. (Prog. Polym. Sci., 2004)

(untitled) - Maatz, G.; Maciollek, A.; Ritter, H. (Beilstein J. Org. Chem., 2012)

(untitled) - Fleischmann, C.; Ritter, H. (Macromol. Rapid Commun., 2013)

(untitled) - Tomatsu, I.; Hashidzume, A.; Harada, A. (J. Am. Chem. Soc., 2006)

(untitled) - Kim, H. N.; Guo, Z.; Zhu, W.; Yoon, J.; Tian, H. (Chem. Soc. Rev., 2011)

(untitled) - Kim, J.-M.; Lee, J.-S.; Lee, J.-S.; Woo, S.-Y.; Ahn, D. J. (Macromol. Chem. Phys., 2005)

(untitled) - Yuen, F.; Tam, K. C. (Soft Matter, 2010)

(untitled) - Wang, S.; Shen, S.; Xu, H. (Dyes Pigm., 2000)

(untitled) - Song, H.-F.; Chen, K.-C.; Wu, D.-Q.; Tian, H. (Dyes Pigm., 2004)

(untitled) - Park, J. S.; Jeong, S.; Dho, S.; Lee, M.; Song, C. (Dyes Pigm., 2010)

(untitled) - Park, J.; Jeong, S.; Ahn, B.; Kim, M.; Oh, W.; Kim, J. (J. Inclusion Phenom. Macrocyclic Chem., 2011)

(untitled) - Lee, E.-M.; Gwon, S.-Y.; Ji, B.-C.; Kim, S.-H. (J. Lumin., 2011)